Electrochemical Disposable Printed Aptasensor for Sensitive Ciprofloxacin Monitoring in Milk Samples - Daniela Nunes da Silva; Thaís Cristina de Oliveira Cândido; Arnaldo César Pereira (Chemosensors)
An electrochemical aptasensor was developed for the rapid and sensitive detection of ciprofloxacin (CPX) in milk samples. The device was fabricated on a polyethylene terephthalate (PET) substrate using a screen-printing technique with carbon-based conductive ink. Gold nanoparticles (AuNPs) were incorporated to enhance aptamer immobilization and facilitate electron transfer at the electrode surface. The sensor’s analytical performance was optimized by adjusting key parameters, including AuNP volume, DNA aptamer concentration, and incubation times for both the aptamer and the blocking agent (6-mercapto-1-hexanol, MCH). Differential pulse voltammetry (DPV) measurements demonstrated a linear response ranging from 10 to 50 nmol L−1 and a low detection limit of 3.0 nmol L−1. When applied to real milk samples, the method achieved high recovery rates (101.4–106.7%) with a relative standard deviation below 3.1%, confirming its robustness. This disposable and cost-effective aptasensor represents a promising tool for food safety monitoring, with potential for adaptation to detect other pharmaceutical residues in dairy products.